2021
DOI: 10.2147/jbm.s340361
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Led Acute Heart Failure Managed Successfully with Immunosuppression

Abstract: Macrophage activation leading to multi-organ dysfunction/failure has been described in various hematologic disorders like hemophagocytic lympho-histiocytosis (HLH), also known as macrophage activation syndrome (MAS) and macrophage activation like syndrome (MALS). Congestive heart failure (CHF) appears to be an uncommon manifestation of macrophage activation. This novel entity of macrophage activationassociated cytokine-mediated CHF has not been well reported in the medical literature. We report two young femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Thus, this association to HLH may be merely coincidental, and these underlying conditions are probably not related to HLH. Such results are consistent with the literature on HLH that does not list these causes as underlying causes, at least not frequently [ 23 , 24 ]. This study has several limitations.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, this association to HLH may be merely coincidental, and these underlying conditions are probably not related to HLH. Such results are consistent with the literature on HLH that does not list these causes as underlying causes, at least not frequently [ 23 , 24 ]. This study has several limitations.…”
Section: Discussionsupporting
confidence: 92%
“…Yet there are not many case reports of heart failure caused by MAS available in the literature. In recent years, only a handful of such cases were reported: one paper describing a decompensated right heart failure [ 8 ], one presenting two cases of acute heart failure treated with immunosuppression [ 9 ], and one case report of fatal acute heart failure reported by our team [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear therapeutic protocols for MAS, but numerous studies have shown the effectiveness of high-dose corticosteroids, calcineurin inhibitors (cyclosporine), followed by etoposide, cyclosporine, i.v. immunoglobulins, antithymocyte globulin, or biologic drugs such as IL-1 or IL-6 inhibitors [ 2 , 8 , 9 ]. Some authors distinguish an entity similar to MAS called the macrophage activation-like syndrome (MALS), specifically in critically ill patients with sepsis rapidly progressing to an early death.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-cytokine drugs may be a promising strategy in the development of cardiovascular pharmacotherapy, especially when included as part of a personalized approach [14,15]. The introduction of these types of drugs is an additional argument in support of the pro-inflammatory etiology of cardiovascular diseases and to reduce inflammation-related residual CVD risk.…”
Section: Introductionmentioning
confidence: 99%